Tools and approaches to operationalize the commitment to equity, gender and human rights: towards leaving no one behind in the Sustainable Development Goals - Gerardo Zamora; Theadora Swift Koller; Rebekah Thomas; Mary Manandhar; Eva Lustigova; Adama Diop; Veronica Magar (Taylor & Francis Group, 2018)
The objective of this article is to present specific resources developed by the World Health Organization on equity, gender and human rights in order to support Member States in operationalizing their commitment to leave no one behind in the health Sustainable Development Goals (SDGs), and other health-related goals and targets. The resources cover: (i) health inequality monitoring; (ii) barrier analysis using mixed methods; (iii) human rights monitoring; (iv) leaving no one behind in national and subnational health sector planning; and (v) equity, gender and human rights in national health programme reviews. Examples of the application of the tools in a range of country contexts are provided for each resource.